2016
DOI: 10.1108/caer-09-2015-0115
|View full text |Cite
|
Sign up to set email alerts
|

Transportation infrastructure and rural development in China

Abstract: Purpose The infrastructure investment is one important source of economic growth in China in the past three decades. However it is not clear to what extent such investment affects development in rural area. The purpose of this paper is to explore this impact both conceptually and quantitatively, and draw policy implications from the empirical exercise. Design/methodology/approach The authors first describe the conceptual link between the transportation infrastructure and rural development, which motivates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 17 publications
(15 reference statements)
0
13
1
Order By: Relevance
“…Finally, the RAI variable has a slightly strong negative role in stimulating farmland conversion in the first delayed value (t -1) in China. This result getting a different result with study did by Wang and Sun (2016) which found that investment in transportation infrastructure affects rural development in China positively. Regarding cereal yield, a 1 percent increase in the road infrastructure (road length) leads to around 0.05 percent increase in cereal yield in the short-, and approximately 0.19 percent increase in the long-run.…”
Section: In the Short-runcontrasting
confidence: 58%
“…Finally, the RAI variable has a slightly strong negative role in stimulating farmland conversion in the first delayed value (t -1) in China. This result getting a different result with study did by Wang and Sun (2016) which found that investment in transportation infrastructure affects rural development in China positively. Regarding cereal yield, a 1 percent increase in the road infrastructure (road length) leads to around 0.05 percent increase in cereal yield in the short-, and approximately 0.19 percent increase in the long-run.…”
Section: In the Short-runcontrasting
confidence: 58%
“…Based on state-owned and non-stateowned manufacturing enterprise data, Li and Li (2013) employ an economic order quantity model and find that regional road investment contributed 11.5 percent to firms' productivity growth on average during the period 1998-2007. Applying an autoregressive distributed lag model on rural household data from 1980-2013, Wang and Sun (2016) find that transportation infrastructure has positive effects on regional development. Finally, Ansar et al (2016) find weak evidence of a profitable effect of infrastructure investment.…”
Section: Introductionmentioning
confidence: 98%
“…For instance, when a road project is delayed, it hampers easy access to the urban market. This compels the local businessman to use alternate transport, which is not only costly for them but also time-consuming [81]. Thus, there is an increase in the price of consumer goods and major food commodities.…”
Section: Increases the Price Of Consumer Goods (Ecf_9)mentioning
confidence: 99%